State, community, and local development in Nigeria - Francis, Paul A.; Akinwumi, James Adewuyi (Washington, D.C. : The World Bank, 1996)
This study presents the results of consultative surveys examining local organizations in thirty-six rural and urban communities across Nigeria.
Includes bibliographical references (p. 53-55).
osa 17/08/16
Loans
Keywords: Community development; Community organization; Non-governmental organizations; Poor